Prevalencia de tuberculosis pulmonar y extrapulmonar en usuarios de Centros de Salud del cantón Huaquillas provincia de El Oro - Ochoa Ramón, Luz Valeria (2023)
Tuberculosis is an infection caused by Mycobacterium tuberculosis, it produces the highest mortality in the world and can mainly impact young adults in their productive years; however, it can affect all age groups. Tuberculosis can be divided into two forms: pulmonary and extrapulmonary tuberculosis. In pulmonary tuberculosis, the respiratory tract is its main route of entry into the body. On the other hand, extrapulmonary tuberculosis occurs in other organs and is less frequent due to the location of the organs that it can affect. Therefore, we focused on determining the prevalence of tuberculosis of pulmonary and extrapulmonary tuberculosis in users who attended the La Merced and La Paz Health Centers of the Huaquillas canton, El Oro province, 2018-2020. The present study had a quantitative approach of a nonexperimental, retrospective, and correlational type; made up of records of patients with positive smear test results, diagnosis of pulmonary or extrapulmonary tuberculosis, and resistance to antituberculosis treatment; the Jamovi program was used for statistical processing. A prevalence of 87.7% was obtained for pulmonary tuberculosis and 12.3% for extrapulmonary tuberculosis; a frequency of tuberculosis in the male sex of 76.7% was demonstrated followed by the female sex with 23.3%; according to the age group, there was a higher percentage in the range of 20-64 years with 68.5%; it was recorded that 33% presented resistance to the drug isoniazid. In conclusion, 2019 showed a higher prevalence of tuberculosis, considering some variables that were studied such as age and sex